Sertifikasi Halal Suatu produk Skincare dalam Perspektif Fiqh Kontemporer - Ningsih, Febri Adelia; Sumantri, Sonya Noprisa; Fachri , Syacharani Aulia; Sabrina, Shafiyah; Ahmad Sukry Daulay (Albayan Journal of Islam and Muslim Societies, 2024)
Halal certification in skincare products is gaining increasing importance in line with the rising public awareness of the need for products that comply with Sharia principles. The perspective of contemporary Islamic jurisprudence (fiqh) plays a significant role in shaping opinions regarding the use of various ingredients in cosmetic products, including skincare. This perspective integrates traditional fiqh principles with the demands of modern times, particularly in evaluating controversial substances such as alcohol commonly found in cosmetics. Contemporary fiqh highlights that, beyond the halal status of ingredients, aspects of health and safety must also be given primary consideration. Halal certification not only provides assurance of religious compliance but also affirms the safety of the product for consumers. However, challenges persist in its implementation, notably in relation to marketing overclaims and the use of non-standardized ingredients. Strengthening consumer education and regulatory oversight are thus essential strategies for ensuring the sustainability and effectiveness of halal certification in the cosmetic industry.